Measurement and instrumentation : theory and application - Morris, Alan S.; Langari, Reza (Amsterdam [etc.] Elsevier, 2016)
Measurement and Instrumentation introduces undergraduate engineering students to the measurement principles and the range of sensors and instruments that are used for measuring physical variables. Based on Morris?s Measurement and Instrumentation Principles, this brand new text has been fully updated with coverage of the latest developments in such measurement technologies as smart sensors, intelligent instruments, microsensors, digital recorders and displays and interfaces. Clearly and comprehensively written, this textbook provides students with the knowledge and tools, including examples in LABVIEW, to design and build measurement systems for virtually any engineering application. The text features chapters on data acquisition and signal processing with LabVIEW from Dr. Reza Langari, Professor of Mechanical Engineering at Texas A&M University.
Keywords: Medición -- Aparatos e instrumentos; Control automático